Job Quality and Its Consequences For The Workforce of Large, Medium-Sized, and Public-Sector Companies in Argentina - Jiménez, Mónica (2017)
This article aims to investigate whether this labor heterogeneity within large, medium-sized and public-sector companies (MGEySP) during 1995-2014 could have generated a more complex segmentation related to the existence of formal and informal workers. For this segmentation, different scenarios are analyzed considering the characteristics of jobs based on the notion of job quality introduced by ILO (2002). The period under study allows consideration of different labor, economic and social settings. Although more than 78% of workers work for MGEySP, the literature has paid little attention to them because of the assumptions that are made about their features and operation. Also, this paper questions the studies in Argentina which argue that labor segmentation occurs only as a result of informal employment or employment within the informal sector. The evidence confirms some assumptions made about segmentation and the presence of a complex structure.